2016
DOI: 10.1111/mve.12191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of white‐tailed deer on the spread of Borrelia burgdorferi

Abstract: There is a public perception that the white-tailed deer Odocoileus virginianus (Artiodactyla: Cervidae) is the main reservoir supporting the maintenance and spread of the causative agent of Lyme disease, Borrelia burgdorferi. This study examines the pathogen prevalence rate of Borrelia in adult Ixodes scapularis (Ixodida: Ixodidae), the black-legged tick, collected from white-tailed deer and compares it with pathogen prevalence rates in adult ticks gathered by dragging vegetation in two contiguous counties wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The general factors driving the escalation of Lyme disease, however, are similar in North America, Europe, and Asia, irrespective of differences in habitat, hosts, and behavior (Mannelli et al 2012, Kulkarni et al 2015, Medlock and Leach 2015. These factors, discussed below, include climate change (Ostfeld and Brunner 2015), host and reservoir expansion (Diuk-Wasser et al 2012, Roy-Dufresne et al 2013, Roome et al 2017, and enhanced monitoring, detection, and reporting of Ixodes spp. and Lyme disease (e.g., Aenishaenslin et al 2016).…”
Section: Factors Driving Lyme Disease Expansion: Vectors Hosts and mentioning
confidence: 99%
See 1 more Smart Citation
“…The general factors driving the escalation of Lyme disease, however, are similar in North America, Europe, and Asia, irrespective of differences in habitat, hosts, and behavior (Mannelli et al 2012, Kulkarni et al 2015, Medlock and Leach 2015. These factors, discussed below, include climate change (Ostfeld and Brunner 2015), host and reservoir expansion (Diuk-Wasser et al 2012, Roy-Dufresne et al 2013, Roome et al 2017, and enhanced monitoring, detection, and reporting of Ixodes spp. and Lyme disease (e.g., Aenishaenslin et al 2016).…”
Section: Factors Driving Lyme Disease Expansion: Vectors Hosts and mentioning
confidence: 99%
“…As these species rarely bite humans, they pose little risk of transmitting the Lyme disease pathogen. However, these other tick species play an important role in maintaining B. burgdorferi in nature ( James and Oliver 1990, Hornok et al 2012, Roome et al 2017. Ixodes spp.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that tick populations have increased as a result of increases in deer populations (Scharlemann et al, 2008), however deer can clear B. burgdorferi s.l. from ticks and therefore this may not be responsible for the increase in Lyme borreliosis (Roome et al, 2017). Up to 2000 cases annually are thought to go undiagnosed (British Infection Association, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…duguesi specimen retrieved from jaguars, cattle, ringtails and rabbits have been shown to test positive for Borrelia ( S2 Table ). The analysis of diverse wild and domestic animal species is relevant, since they could be playing a role as maintenance hosts for ticks in the ecosystem, as has been evidenced in white-tailed deer [ 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%